2002
DOI: 10.1016/s0301-0104(02)00485-8
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-atom effects on metalloporphyrins and polyhalogenated porphyrins

Abstract: The photophysics of halogenated and metallated tetrakisphenylporphyrins is investigated using single-photon counting, photoacoustic calorimetry and luminescence techniques. The radiationless transition rates in these and related molecules are interpreted with a quantum-mechanical tunnelling model modified to include the effect of spin-orbit coupling in the intersystem crossing rates. It is shown that tetrakisphenylporphyrins with halogens in the ortho positions have long-lived triplet states that are formed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 46 publications
10
120
0
1
Order By: Relevance
“…can induce spin orbit coupling due to the heavy atom effect, thus facilitating intersystem crossing. [16,17] An interesting group of organic chromophores that can be utilized ast riplet photosensitizers are aza-BODIPYs (aza-4,4-difluoro-4-bora-3a,4a-diaza-s-indacene). [18,19] Structurally,a za-BODIPY dyes are derivatives of BODIPY (4,4-difluoro-4-bora3a,4a-diaza-s-indacene) dyes obtained by replacing the mesocarbona tom that connects both pyrrole rings with an azabridge.…”
Section: Introductionmentioning
confidence: 99%
“…can induce spin orbit coupling due to the heavy atom effect, thus facilitating intersystem crossing. [16,17] An interesting group of organic chromophores that can be utilized ast riplet photosensitizers are aza-BODIPYs (aza-4,4-difluoro-4-bora-3a,4a-diaza-s-indacene). [18,19] Structurally,a za-BODIPY dyes are derivatives of BODIPY (4,4-difluoro-4-bora3a,4a-diaza-s-indacene) dyes obtained by replacing the mesocarbona tom that connects both pyrrole rings with an azabridge.…”
Section: Introductionmentioning
confidence: 99%
“…19, 20 For example, it has been reported that the triplet quantum yield, Φ T , for meso-tetrakis (2,6-dichloro- † Dedicated to Professor Sebastião Formosinho on the occasion of his 60th birthday.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of U D value with the insertion of more bromine atoms was already predicted for the Zn(II) complex of halogenated methoxyporphyrins [8]. The substitution in both ortho and para positions (PS4) has a negative effect on the singlet oxygen formation quantum yield.…”
Section: Discussionmentioning
confidence: 59%
“…With other halogen atoms some reports confirmed the expected superior behaviour for singlet oxygen formation, as expected from the heavy atom effect [8,32] but photocytoxicity was not studied.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation